Beispiel Nr: 19
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1x +1y =2\\ 3x +3y = 3 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 1 x +1 y =2\\ II \qquad 3 x +3 y = 3 \\ \text{I nach x auflösen}\\ 1 x +1 y =2 \\ 1 x +1 y =2 \qquad /-1 y\\ 1 x =2 -1 y \qquad /:1 \\ x =2 -1 y \\ \text{I in II}\\ 3 (2 -1 y ) + 3 y = 3 \\ 6 -3 y +3 y = 3 \qquad / -6 \\ -3 y +3 y = 3 -6 \\ \\ L=\{\}\end{array} & \begin{array}{l} I \qquad 1 x +1 y =2\\ II \qquad 3 x +3 y = 3 \\ \text{I nach y auflösen}\\ 1 x +1 y =2 \\ 1 x +1 y =2 \qquad /-1 x\\ 1 y =2 -1x \qquad /:1 \\ y =2 -1x \\ \text{I in II}\\ 3x + 3(2 -1 x ) = 3 \\ 6 -3 x +3 x = 3 \qquad / -6 \\ -3 x +3 x = 3 -6 \\ \\ L=\{\}\end{array} \end{array} $